Understanding the Role of Social Factors in Farmworker Housing and Health. (November 2015) - Marsh, Ben; Milofsky, Carl; Kissam, Edward; Arcury, Thomas A.
Differences in social advantage significantly influence health conditions and life expectancy within any population. Such factors reproduce historic class, race, and ethnic disparities in community success. Few populations in the United States face more social and economic disadvantage than farmworkers, and farmworker housing has significant potential to ameliorate or amplify the health impact of those disadvantages. Drawing on the limited direct research on farmworkers, and on additional research about poor, isolated, and immigrant societies, we propose four mechanisms through which housing can be expected to affect farmworker health: quality of social capital within farmworker communities, stress effects of poor housing situations, effects of housing on social support for healthy behaviors, and interactions among these factors, especially effects on children that can last for generations. Policy and planning definitions of "adequate" farmworker housing should take a more holistic view of housing needs to support specific social and community benefits in design decisions.